A cerium-based fluorescent nanosensor for highly specific detection of glutathione over cysteine and homocysteine. Issue 1 (3rd November 2020) - Wang, Tianlin; Tao, Zhanhui; Qu, Chi; Wang, Shuo; Liu, Yaqing
Abstract : A green synthesis of a novel Ce-based nanomaterial with fluorescence activity for highly sensitive and specific GSH detection. Abstract : Ever-increasing attention has been focused on constructing a sensing system for specific detection of glutathione (GSH) over cysteine (Cys) and homocysteine (Hcy), which usually interfere with the GSH detection due to their similar structures and the presence of thiol groups in these amino acids. Here, a novel fluorescence-sensing system is developed for highly specific GSH detection over Cys and Hcy. The sensing system is constructed through facilely mixing dipicolinic acid (DPA) and guanosine 5′-monophosphate (GMP) with cerium acetate at ambient conditions, denoted as DPA-Ce-GMP. The resultant DPA-Ce-GMP possesses fluorescence emission with excellent thermal stability and anti-light bleaching, which can be quenched by copper ions (Cu 2+ ). The GSH, and not Cys or Hcy, can trap Cu 2+ from DPA-Ce-GMP, resulting in the restoration of the fluorescence of the sensing system. The limit of detection reaches as low as 7.1 nM. The GSH detection in a real sample of human serum was further explored and exhibits satisfactory recovery. The developed sensing system has the advantages of ease-of-preparation, excellent selectivity and stability, demonstrating its potential application in disease diagnosis in the future.